Impact of Innovation on Market Share of Small and Medium Enterprises (SMEs) in Abuja - Ehiaguina, Judith Aimiebenomo; Sijibomi, Olubodun; Yakubu, Fredrick Seun; Ediuku, Ekanem (British Journal of Marketing Studies, 2025)
This study investigates the impact of innovation encompassing product and service innovation (PSI), process innovation (PI), and marketing innovation (MI) on the market share of small and medium-sized enterprises (SMEs) in Abuja, Nigeria. Using a cross-sectional survey of 347 SMEs and applying multiple regression analysis, the results reveal that PSI and PI significantly enhance market share, with PSI emerging as the strongest driver. A one-unit increase in PSI leads to a 0.637-unit increase in market share, while PI contributes a 0.305-unit increase. In contrast, MI does not have a statistically significant standalone effect on market share, suggesting its role as a complementary strategy. These findings underscore the critical importance of innovation for SME competitiveness, highlighting the need for Abuja-based SMEs to prioritise product and process innovations while leveraging marketing strategies as supportive tools. The study contributes to the understanding of how innovation strategies can be tailored to the unique socio-economic context of Abuja to sustain growth and market competitiveness.